Ship Heading Control of USV using Model Predictive Control - Tahiyatul Asfihani, Baity Jannaty, Erna Apriliani, Subchan, Daniel M. Rosyid, Aries Sulisetyono, Dieky Adzkiya (International Journal of Advanced Science and Technology, 2020)
This paper focuses on control design of a Unmanned Surface Vehicle (USV). The objective is that the USV’s heading angle has to follow a desired angle, while minimizing the energy usage. Here, the energy is used to move the rudder of the USV. The input variable is the rudder angle. Model Predictive Control (MPC) is applied to obtain the controller. The computational results show that  the  obtained  controller  is  able  to  control  the USV’s heading angle to the desired angle. Four scenarios   are simulated and discussed and the best performance (i.e. the smallest error) is achieved.Index Terms: Unmanned Surface Vehicle (USV), Model Pre- dictive Control (MPC), ship’s heading angle, rudder angle